The impact of internship experience on students’ career intentions in hospitality education - Prameswari, Made Bintang Nadiva (Review of Management, Accounting, and Business Studies, 2025)
Hospitality, as a major segment of the tourism industry, relies heavily on effective human resource management to deliver service quality and sustain organizational competitiveness. Consequently, workforce demand in the hospitality sector must be supported by a pipeline of skilled and job-ready graduates, which can be strengthened through vocational education and structured internship programs. Bali Tourism Polytechnic (Politeknik Pariwisata Bali) implements an internship program known as Praktek Kerja Nyata (PKN) across all study programs, including Hospitality Administration. Internship participation is expected to enhance students’ professional competencies and provide clearer insights into career options during and after their studies.This study examines the effect of internship experience on the career intention of Hospitality Administration students at Bali Tourism Polytechnic. Using a quantitative approach, data were collected through an online questionnaire measuring students’ satisfaction with their internship experience and their career intention. The survey targeted students in semesters 4, 6, and 8 who had completed at least one internship placement. A simple random sampling technique yielded 253 valid responses. Data were analyzed using simple linear regression, t-tests, and the coefficient of determination. From a management perspective, the findings underscore the role of internship programs as a strategic human resource practice for shaping early career intentions in the hospitality industry. The results indicate that internship experience has a positive and statistically significant effect on students’ career intention, explaining 45.8% of the variance. These findings highlight the managerial importance of well-designed internship programs for human resource development and workforce planning in the hospitality sector.